Vγ9Vδ2 TCR‐activation by phosphorylated antigens requires butyrophilin 3 A1 (BTN3A1) and additional genes on human chromosome 6. Issue 9 (30th June 2014) - Riaño, Felipe; Karunakaran, Mohindar M.; Starick, Lisa; Li, Jianqiang; Scholz, Claus J.; Kunzmann, Volker; Olive, Daniel; Amslinger, Sabine; Herrmann, Thomas
<x xml:space="preserve">Abstract</x> Pyrophosphorylated metabolites of isoprenoid‐biosynthesis (phosphoantigens, PAgs) activate Vγ9Vδ2 T cells during infections and trigger antitumor activity. This activation depends on expression of butyrophilin 3 A1 (BTN3A1) by antigen‐presenting cells. This report defines the minimal genetic requirements for activation of Vγ9Vδ2 T cells by PAgs and mAb 20.1. We compared PAg‐presentation by BTN3A1‐transduced CHO hamster cells with that of CHO cells containing the complete human chromosome 6 (Chr6). BTN3A1 expression alone was sufficient for activation of Vγ9Vδ2 T‐cell receptor transductants by mAb 20.1., while activation by PAgs also required the presence of Chr6. We take this finding as evidence that gene(s) on Chr6 in addition to BTN3A1 are mandatory for PAg‐mediated activation of Vγ9Vδ2 T cells. This observation is important for the design of animal models for PAg‐mediated immune responses and provokes speculations about the analogy between genes controlling PAg presentation and MHC‐localized genes controlling peptide‐antigen presentation.